Simulasi Dan Deteksi Gangguan Belitan Stator Motor Induksi Tiga Fasa Menggunakan Arus Starting Dengan Matlab/Simulink - Jusni Sufrianti; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Induction motors are electric motors are the most widely used in industry, therefore the performance, stability and efficiency of an induction motor is of considerable concern to anticipate disturbances that could lead to a decrease in the age of the induction motor. Motor Current Signature Analysis (MCSA) is one of the most common method used to detect the motor's performance on-line, but the use of this MCSA not give less good results when the load torque is not constant. Modeling the induction motor in a state of no interference derived from mathematical equations with the method of the reference frame stator (stationary reference frame). In this paper, interference with the stator winding is detected by a change in resistance and inductance then and the emergence of sideband frequencies / other at the starting stator current spectrum, then do the phase characteristic approach todiagnosis techniques Fast Fourier Transform (FFT). Analytical results from the use of such techniques show an increase the amount of energy in each frequency band and a large rangeTHD each interruption, so that the motor condition can be known whether normal or damage occurs.Keywords - induction motor, the stator windings, short circuit, Fast Fourier Transform, software matlab